Blood mineral profile of normal cyclic and repeat breeder crossbred cows under rural condition - DAS, S; BANDOPADHYA, S K; BASU, S; GHOSH, B B; DAITAGUPTA, R (The Indian Journal of Animal Reproduction, 2023)
The serum calcium. inorganic phosphorus, copper, zinc. iron and maganese were estimated in 22 repeatbreeder and 12 normal cyclic crossbred cows. Repeat breeder cows had significantly lower inorganic P (4.729±0.150mg; I 00 ml), Cu (0.96±0.017 μg, ml) and Zn ( 1.80±0.033 μg/ml) than normal cyclic cows where the levels were5.513±0.265 mg/ I 00 ml, 0.97±0.023 μg/ml and 2.09±0.057 μg/ml , respectively. Higher serum iorn level was found inthe repeat breeders (3.594±0.043 μg,1ml) than normal cyclic cows (3.424±0.053 μg/ml). No significant variationhowever. was found in Ca and Mn between the groups.
Keywords: Repeat breeder; crossbred cow; mineral profile